Quartz microfill dispersion optimisation - N. M. Tolypina; E. N. KHakhaleva; D. A. Tolypin (Вестник СибАДИ)
Introduction. One of the problems of developing new generation concrete is to ensure the rational granulometric composition of a mixture of cement and fine additives to ensure the densest packing of all particles of the cement system. In this regard, the paper considers the optimization of the dispersed structure of quartz filler, taking into account its specific surface area, concentration in the composition of the binder and water-solid ratio.Materials and methods. In the studies, Portland cement TSEM I 42.5 N (GOST 31108-2020) of ZAO Belgorod Cement and fine quartz were used. The compressive strength samples were tested on a PGM-100 MG4 laboratory press. The granulometric composition of the fillers was determined using Analysette 22 NanoTec plus laser diffraction particle size analyzer.Results. The conducted studies have allowed to determine that the optimal dosages of microdispersion filler are closely related to the specific surface area and the V/T of the mixture. It is shown that with an increase in the dispersion of quartz filler, a decrease in the range of optimal dosages is observed, which narrows with an increase in the water-solid ratio. The mechanisms of structure formation affecting the properties of dispersed-optimized cement systems are described. With the growth of the specific surface of the filler, the specific activity of the unit of the surface of the filled binder decreases, which is accompanied by a decrease in the number of crystallizationcoagulation bonds between the hydrate phases of cement.Conclusion. The experimental data obtained confirm that for a cement stone made of a mixed binder, the watersolid ratio is no less significant than the concentration of a mineral additive, therefore, a decrease in the V/T of mixed cements is a necessary condition for achieving a given strength.